The Many Axes of Deer Lactation - Ceacero, Francisco; García, Andrés J; Landete-Castillejos, Tomás; Komárková, Martina; Hidalgo, Francisco; Serrano, Martina P; Gallego, Laureano (Journal of mammary gland biology and neoplasia, 2016)
In undomesticated animals information about the production and composition of milk over time is still scarce. In general, for most mammals it is known that milk composition changes across lactation, is different for male and female offspring, and even that marsupials, such as kangaroos, can simultaneously produce milk of different compositions for young of different ages. Such parallel milk production of differing compositions has not yet been studied in single-offspring placental mammals, but may help to explain behavioural processes like allosuckling (feeding the young of other adults) and lateralized suckling preferences. In this study we analysed the production and composition of milk in red deer throughout the lactation period and now confirm for the first time that there are axial differences present. The front teats, which are the favoured suckling positions of the deer's offspring, produce milk with a greater protein-to-fat ratio. Also, from the beginning of lactation the yield is greater on the left side, the side preferred by calves in all of the studied species, both at population and individual level. The links between milk production and calf behaviour in deer deserve further study.
Keywords: laktace; Animals; Milk composition; Udders; Female; kojení; zvířata; mléko; Laterality; Lactation; Breast Feeding; Deer; Allosuckling; Milk production; vysoká zvěř; ženské pohlaví; Milk